Ultra‐Specific Isolation of Circulating Tumor Cells Enables Rare‐Cell RNA Profiling. Issue 9 (18th April 2016) - Jack, Rhonda M.; Grafton, Meggie M. G.; Rodrigues, Danika; Giraldez, Maria D.; Griffith, Catherine; Cieslak, Robert; Zeinali, Mina; Kumar Sinha, Chandan; Azizi, Ebrahim; Wicha, Max; Tewari, Muneesh; Simeone, Diane M.; et al.
Abstract : The clinical potential of circulating tumor cells (CTCs) in managing cancer metastasis is significant. However, low CTC isolation purities from patient blood have hindered sensitive molecular assays of these rare cells. Described herein is the ultra‐pure isolation of CTCs from patient blood samples and how this platform has enabled highly specific molecular (mRNA and miRNA) profiling of patient CTCs.